2021
DOI: 10.1021/acsomega.1c01249
|View full text |Cite
|
Sign up to set email alerts
|

Study of Combustion Characteristics and Kinetics of Agriculture Briquette Using Thermogravimetric Analysis

Abstract: The present paper was aimed to investigate the physicochemical properties and combustion characteristics of corn straw briquette as a fuel energy. The results of physicochemical properties displayed that corn straw briquette has higher volatile matter, lower ash content, and higher heating value. Combustion characteristics and kinetic analysis were investigated using thermogravimetry analysis at various heating rates of 10, 15, and 20 °C/min. It was observed that the maximum burning rate shifted to a higher te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…On the other hand, a study on the use of biomass briquette made from corn straw by Liu et al. [35] reported an E a value of 114.4 kJ mol –1 . This validates the energy densification through torrefaction in the use of biomass as an efficient fuel source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a study on the use of biomass briquette made from corn straw by Liu et al. [35] reported an E a value of 114.4 kJ mol –1 . This validates the energy densification through torrefaction in the use of biomass as an efficient fuel source.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that the variation of activation energy for high ash Indian coal increased gradually with respect to conversion and attained a maximum value at α = 0.5, after which a gradual decrease was observed, with a mean E a of 70.5 kJ mol -1 . On the other hand, a study on the use of biomass briquette made from corn straw by Liu et al [35] reported an E a value of 114.4 kJ mol -1 . This validates the energy densification through torrefaction in the use of biomass as an efficient fuel source.…”
Section: Combustion Kineticsmentioning
confidence: 98%
“…It can be found that the moisture content was 7.89%. Volatile matter content was 47.43%, generally considered acceptable for ignition and combustion processes [4,27]. Different from other biomasses, yak manure had a higher ash content (34.36%) [28][29][30].…”
Section: Yak Manure Characteristicsmentioning
confidence: 99%
“…These issues have made the awareness of the development of alternative energy sources an urgent matter. Biomass, as the fourth energy source after coal, oil, and gas, is the most attractive resource for its renewable, huge resources, low cost, and low emissions [4][5][6]. However, the low density, high costs of handling, transportation, and storage inhibit its use [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Briket didefinisikan sebagai perubahan bentuk material yang pada awalnya berupa serbuk atau bubuk seukuran pasir menjadi material yang lebih besar dan mudah dalam penanganan atau penggunaannya [5], [6]. Perubahan ukuran material tersebut dilakukan melalui proses penggumpalan dengan penekanan dan penambahan atau tanpa penambahan bahan perekat [7], [8]. Salah satu limbah yang kurang dimanfaatkan selama ini yaitu ampas kopi.…”
unclassified